Beginning Lua with World of Warcraft addons - Emmerich, Paul.; Safari eBooks (Berkeley, Calif. : Apress ; New York : Distributed to the book trade worldwide by Springer-Verlag New York, 2009)
"Deadly Boss Mods author Paul Emmerich will take you from novice to elite with his approachable, up-to-date guide to building addons for World of Warcraft. Using the powerful Lua scripting language and XML, you'll learn how to build and update powerful mods that will remake your World of Warcraft experience and introduce you to the field of professional software development"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Computer games -- Programming; Lua (Computer program language); World of Warcraft; Electronic books